2016
DOI: 10.1002/anie.201608463
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Resolved In Situ X‐ray Diffraction Reveals Metal‐Dependent Metal–Organic Framework Formation

Abstract: Versatility in metal substitution is one of the key aspects of metal-organic framework (MOF) chemistry, allowing properties to be tuned in a rational way. As a result, it important to understand why MOF syntheses involving different metals arrive at or fail to produce the same topological outcome. Frequently, conditions are tuned by trial-and-error to make MOFs with different metal species. We ask: is it possible to adjust synthetic conditions in a systematic way in order to design routes to desired phases? We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…For example, the MIL‐88 framework with composition [ M III 3 (μ 3 ‐O)(OH)(H 2 O) 2 (BDC‐NH 2 ) 3 ] is formed as intermediate product during the synthesis of the Al‐MOFs [Al(OH)BDC‐NH 2 )] or Al‐MIL‐53‐NH 2 and [Al 3 (μ 3 ‐O)(OH)(H 2 O) 2 (BDC‐NH 2 ) 3 ] or Al‐MIL‐101‐NH 2 as well as during the synthesis of the iron MOF [Fe(OH)BDC)] or Fe‐MIL‐53 . Similarly, in the system M 2+ /DABCO/H 2 BDC ( M 2+ = Co 2+ , Ni 2+ , Cu 2+ or Zn 2+ ; DABCO = diazabicyclo‐[2.2.2]octane and H 2 BDC = terephthalic acid) it was reported that in most cases, initially a kagome framework can be observed, which converts further to a denser square grid lattice with identical composition of [ M II 2 (BDC) 2 (DABCO)] . However, these examples involve exclusively porous solids, retaining the valence of the metal ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the MIL‐88 framework with composition [ M III 3 (μ 3 ‐O)(OH)(H 2 O) 2 (BDC‐NH 2 ) 3 ] is formed as intermediate product during the synthesis of the Al‐MOFs [Al(OH)BDC‐NH 2 )] or Al‐MIL‐53‐NH 2 and [Al 3 (μ 3 ‐O)(OH)(H 2 O) 2 (BDC‐NH 2 ) 3 ] or Al‐MIL‐101‐NH 2 as well as during the synthesis of the iron MOF [Fe(OH)BDC)] or Fe‐MIL‐53 . Similarly, in the system M 2+ /DABCO/H 2 BDC ( M 2+ = Co 2+ , Ni 2+ , Cu 2+ or Zn 2+ ; DABCO = diazabicyclo‐[2.2.2]octane and H 2 BDC = terephthalic acid) it was reported that in most cases, initially a kagome framework can be observed, which converts further to a denser square grid lattice with identical composition of [ M II 2 (BDC) 2 (DABCO)] . However, these examples involve exclusively porous solids, retaining the valence of the metal ion.…”
Section: Resultsmentioning
confidence: 99%
“…Using synchrotron X‐ray radiation, it is possible to measure PXRD patterns with high temporal resolution in‐situ during the synthesis and thus gain important information, especially about the occurring crystalline products. This allows, for example, the identification of crystalline intermediates, which are only short‐lived during the reaction . In addition, the crystallization kinetics can be assessed and compared at different temperatures or using different heating methods .…”
Section: Introductionmentioning
confidence: 99%
“…The apparently greater stability of the phase 6 could result from an increased density and dimensionality of the metal-organic framework due to "polycondensation" of the isolated trinuclear building units {Zn 3 (RCOO) 6 }, found in 5, into infinite chains, featured in 6. Such an important interplay between the thermodynamics and kinetics of the formation of the crystals of MOFs is rarely reported in such chemistry [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This model has the advantage of parameterising nucleation and crystal growth as two separate events and was developed for the hydrothermal formation of zeolites and subsequently used by a number of groups for study of the solvothermal crystallisation of MOFs. 17,19,40 Although we studied the crystallisation of (2) at four different temperatures (90, 100, 110 and 120°C), owing to the limited amount of beamtime available, only at the higher two temperatures did the reactions reach completion. However, we can measure the induction time for the onset of crystallisation for all temperatures by inspection of the crystallisation data and this shows a significant retardation of crystallisation as the reaction temperature is lowered, as shown in Table 1.…”
Section: -19mentioning
confidence: 99%